EFFECT OF SALINITY STRESS ON GERMINITION PERFORMANCE OF MAIZE (Zea mays L.) SEEDS (Agrosys: Journal of Agronomy and Sustainable Crop Systems, 2026)
Corn is one of the main food crops in Indonesia. Several superior varieties such as Advanta Bejo, Bisi 18, and R1 Raja Nusantara have high production, but their resistance to salinity is not stated. Do the three corn varieties have the same resistance to water salinity? This study aims to determine the effect of water salinity levels on seed germination of three corn varieties (Zea mays L.). A two-factor study with NaCl salt solution concentrations of 0%, 0.25%, 0.5%, 0.75%, and 1% was applied to the seed germination of the three corn varieties, and was repeated 5 times in 5 blocks. The germination response to water salinity was observed in the germination rate (KP), the percentage of total normal sprouts (PKNT), the percentage of abnormal sprouts (PKAN), and non-germinated seeds (PBTB), the percentage of strong normal sprouts (PKNK), the percentage of weak normal sprouts (PKNL), the dry weight of normal sprouts (BKKN), the length of normal sprout shoots (PTKN), and the length of normal primary roots of sprouts (PAPKN). The results of the study showed that high water salinity reduced the germination performance of three corn varieties. Increasing NaCl concentrations caused a decrease in seed viability and vigor. The Advanta Bejo variety was more tolerant to salinity stress than the Bisi 18 and R1 Raja Nusantara varieties.